Inside Back Cover: Selective and Wash‐Resistant Fluorescent Dihydrocodeinone Derivatives Allow Single‐Molecule Imaging of μ‐Opioid Receptor Dimerization (Angew. Chem. Int. Ed. 15/2020). Issue 15 (26th February 2020) - Gentzsch, Christian; Seier, Kerstin; Drakopoulos, Antonios; Jobin, Marie‐Lise; Lanoiselée, Yann; Koszegi, Zsombor; Maurel, Damien; Sounier, Rémy; Hübner, Harald; Gmeiner, Peter; Granier, Sébastien; Calebiro, Davide; et al.
Abstract : Highly selective fluorescent ligands derived from the opium poppy were developed by D. Calebiro, M. Decker et al. in their Research Article on page 5958 to investigate whether μ‐opioid receptors (μ‐ORs) can form dimers on the plasma membrane. These compounds exhibit long residence time and high affinity. Applying these chemical tools, single‐molecule microscopy allowed detection of a small fraction of short‐lived homodimers.